Development and Reconstitution of Software Quality Measurement and Evaluation Standards - Zhang, Yangyang; Liu, Xiaojian; Liu, Zengzhi; Li, WenPeng (2018 19th IEEE/ACIS International Conference on Software Engineering, Artificial Intelligence, Networking and Parallel/Distributed Computing (SNPD), 2018)
How to measure and evaluate software quality is one important research subject in the computer software field. For helping people understand, measure and evaluate software quality, International Organization for Standardization (ISO), has been carrying out years of researches on software quality standardization. The thoughts and methods shown in standardization will help people further understand and predict software quality easier. This paper introduces the development process of the international quality standards and gives more focus on the software quality development trends.